﻿Sodium selenite supplementation does not reduce the effectiveness of X-ray irradiation treatment on human cancerous esophageal TE-8 cells - Irma Melyani Puspitasari; Rizky Abdulah (Pensoft Publishers, 2022)
Sodium selenite supplementation at a concentration 50 nM before X-ray irradiation was suggested to protect non-cancerous human esophageal CHEK-1 cells from irradiation-induced damage. This present study investigated those effects on cancerous human esophageal cell line. The human cancer esophageal cell line, TE-8, was cultured and supplemented for the cytotoxicity assay, the GPx-1 activity, the cell viability assay, clonogenic assay and western blot analysis. An apoptosis biomarker, Cleaved PARP, was used. The results show that cell survival post-irradiation of supplemented-cells had the same effect as the cells treated by irradiation only, tended to decrease the cell viability (p=0.27), and decrease the survival rate of cancerous cells (p=1.00). The cleaved PARP level was higher in supplemented-and irradiated- cells than cells with irradiation alone. These results suggest that 50 nM sodium selenite supplementation prior to irradiation does not reduce the effectiveness of irradiation treatment on cancerous cells.